The Relationship Between Sunscreen Application and Severity Of Melasma - Putri, Intan Annisa; Ardiana, Dian; Tehupuring, Sihning E.J (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Backgrounds: Melasma is commonly observed in community among women of reproductive age. Incidence of melasma at least nine times higher in women than men, especially in pregnant women. The relationship between sunscreen application and melasma in women of reproductive age has not been widely studied and the correlation is not clear. This study aims to determine the relationship between sunscreen use and severity of melasma in women of reproductive age. Methods: An analytical observational cross-sectional study was conducted among 31 women of productive age. Results: The results showed that 14 respondents had good sunscreen usage habit (45.2%), whereas 17 respondents had sun protector irregularly (54.8%). A total 27 respondents (74.2%) had mild melasma, whereas 3 respondents had moderate melasma (22.6%) and 1 respondent had severe melasma (3.2%). The Chi-Square test shows that the significance value (p) = 0.000 (p <0.05) so that there is a significant relationship. Conclusions: Meaning that there is a relationship between the use of sunscreen and severity of melasma in women of reproductive age.